Multiple jets in the Malvinas Current - Piola, Alberto Ricardo (2013)
[1] The velocity structure of the Malvinas Current is described based on the analysis of high-resolution hydrographic data and direct current observations. The data show that though the current width exceeds 150 km, the flow is concentrated in two relatively narrow (~10–20 km) jets. Within these cores, the direct observations indicate surface velocities exceeding 0.5 m.s−1. Surface drifter, satellite-derived mean dynamic topography, and sea surface temperature data suggest that the high-velocity jets are also ubiquitous features of the time mean circulation. Both jets appear to be continuous features extending more than 900 km along the western slope of the Argentine Basin. These jets closely follow the 200 and 1400 m isobaths. Additional high-velocity cores are apparent in direct current measurements and hydrographic observations, but these features are weaker and not continuous along the slope. Though the Malvinas Current transport is mostly barotropic, baroclinic jets are also identified in relative geostrophic velocity sections. The baroclinic jets are colocated with the barotropic jets. Our results suggest that the main Malvinas Current core is located over a relatively flat portion of the bottom, referred to as the Perito Moreno terrace. This observation is in agreement with recent seismic and geological evidence suggesting that in geological time scales the Malvinas Current played a key role in the configuration of the bottom sediments over the western slope of the Argentine Basin.